Fostering Residential Demand Response through Developing Proactive and Elastic Demand Approaches. An Overview DR (Global Journals of Research in Engineering, 2018)
Demand response (DR) is one of the major stakeholders in the smart grid and has been used as an energy reconciler between supply and demand. After a literature overview, the importance of the paper is enhanced by having a theoretical and behavioral-based analysis of DR in power systems. In this work, the potential factors that influence more DR among customers and the residential market as a whole have been discussed. The customers#x2019; elastic demand approach can pave the way for adapting a responsive demand mechanism that ensures the system reliability and cost effective measures. Alternatively, this approach can make the program more effective and supportive in serving the social welfare as whole.
Keywords: demand response; demand elasticity; pricebased demand response; incentive-based response; customer behavior